ACCULTURATION STRESS AMONG LATIN AMERICAN IMMIGRANTS RESIDING IN THE UNITED STATES VS. SPAIN: A LITERATURE REVIEW - Zarza González, María José; Sobrino Prados, María Isabel (Anales de Psicología / Annals of Psychology, 2007)
Spain and the United States are both experiencing a high influx of Latin-American immigrants. Although these countries differ in their history of immigration, policies, resources and the barriers encountered by Latino immigrants, they also face similar challenges. Both countries share growing needs for mental health services, prevention programs and the development of culturally sensitive assessment tools for this emerging population. The main goal of this review is to learn from the long history of and lessons learned from Latin American immigration in the United States. Their extant theories and technology (assessment tools and intervention programs) are extremely valuable for Spanish researchers and clinicians. The recommendations for further research and the develop-ment of intervention programs include the following: 1) explaining the Latino Health Paradox phenomena in the United States, 2) describing this phenomena in Spain 3) conducting studies on risk and protective factors, including comparative studies between both countries, 4) conducting an exhaustive literature review on intervention programs in both countries, and 5) developing culturally appropriate assessment tools and intervention models. In addition to this, we recommend that clinicians conduct assessments and clinical interventions within an ecological approach by respecting the culture, socioeconomic situation and needs of Latino immi-grants.